Experiences Implementing a Suite of Decision Aids for Implantable Cardioverter Defibrillators: Qualitative Insights From the DECIDE-ICD Trial. Issue 11 (15th November 2022) - Knoepke, Christopher E.; Wallace, Bryan C.; Allen, Larry A.; Lewis, Carmen L.; Gupta, Sanjaya K.; Peterson, Pamela N.; Kramer, Daniel B.; Brancato, Scott C.; Varosy, Paul D.; Mandrola, John M.; Tzou, Wendy S.; Matlock, Daniel D.
Abstract : Background: Shared decision making (SDM) is gaining importance in cardiology, including Centers for Medicare & Medicaid Services (CMS) reimbursement policies requiring documented SDM for patients considering primary prevention implantable cardioverter defibrillators. The DECIDE-ICD Trial (Decision Support Intervention for Patients offered implantable Cardioverter-Defibrillators) assessed the implementation and effectiveness of patient decision aids (DAs) using a stepped-wedge design at 7 sites. The purpose of this subanalysis was to qualitatively describe electrophysiology clinicians' experience implementing and using the DAs. Methods: This included semi-structured individual interviews with electrophysiology clinicians at participating sites across the US, at least 6 months following conversion into the implementation phase of the trial (from June 2020 through February 2022). The interview guide was structured according to the RE-AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance [implementation evaluation model]) framework, assessing clinician experiences, which can impact implementation domains, and was qualitatively assessed using a mixed inductive/deductive method. Results: We completed 22 interviews post-implementation across all 7 sites. Participants included both physicians (n=16) and other clinicians who counsel patients regarding treatment options (n=6). While perception of SDM and the DA were positive, participants highlighted reasons for uneven delivery of DAs to appropriate patients. The CMS mandate for SDM was not universally viewed as associating with patients receiving DA's, but rather (1) logistics of DA delivery, (2) perceived effectiveness in improving patient decision-making, and (3) match of DA content to current patient populations. Remaining tensions include the specific trial data used in DAs and reconciling timing of delivery with when patients are actively making decisions. Conclusions: Clinicians charged with delivering DAs to patients considering primary prevention implantable cardioverter defibrillators were generally supportive of the tenets of SDM, and of the DA tools themselves, but noted several opportunities to improve the reach and continued use of them in routine care. Registration: URL: https://www.clinicaltrials.gov ; Unique Identifier: NCT03374891.